Effect of infertility on quality of life of women: a validation study of the Turkish FertiQoL. (2nd July 2016) - Dural, Ozlem; Yasa, Cenk; Keyif, Betul; Celiksoy, Harika; Demiral, Irem; Yuksel Ozgor, Bahar; Gungor Ugurlucan, Funda; Bastu, Ercan
Abstract: The fertility quality of life (FertiQoL) measure specifically evaluates the impact of fertility problems in various life areas. The aim of this study was to examine the relationship between FertiQoL and the hospital anxiety and depression scale (HADS) in the Turkish population. All female patients who underwent various fertility treatments in our infertility clinic from May 2011 to May 2014 were approached to participate in the study and 389 completed the questionnaires. Our results showed that the four core scales of the FertiQoL measure had a Cronbach's α value that was between 0.70 and 0.89. Two scales (anxiety and depression) of HADS both had a Cronbach's α value of 0.80. These values present a reliable usage of FertiQoL and HADS measures (α > 0.60). Significant negative correlations were found between the FertiQoL scales and HADS scales, ranging from −0.27 (between relational scale of FertiQoL and anxiety scale of HADS) to −0.65 (between mind–body scale of FertiQoL and depression scale of HADS). The results of this study provide supportive data to confirm that the Turkish version of FertiQol can accurately evaluate QoL in women who seek fertility treatment in Turkey.